Uniform Convergence Rate of the SNP Density Estimator and Testing for Similarity of Two Unknown Densities - KIM, Kyoo-il (Institutional Knowledge at Singapore Management University, 2006)
This paper studies the uniform convergence rate of the turncated SNP (semi-nonparametric) density estimator. Using the uniform convergence rate result we obtain, we propose a test statistic testing the equivalence of two unknown densities where two densities are estimated using the SNP estimator and supports of densities are possibly unbounded.